Perbedaan Tantangan Kurikulum Dalam Pembentukan Karakter Religius Di Sma Negeri 2 Sangatta Utara - Zahra, Zaitun; Rahmah, Aisyah Nur; Pandiangan, Anjani Putri Belawati (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
Significant changes in curriculum policy result in educational institutions and educators experiencing few obstacles in their adjustments to both learning and learning tools, such as the challenges faced in one school in East Kutai. The aim of this research is to determine the differences in curriculum challenges in forming religious character at SMA Negeri 2 Sangatta Utara. This research uses a qualitative research method with a description type, where the data obtained will be presented in the form of descriptions and illustrations. The results of this research are several challenges faced by educators in each curriculum implementation in forming religious character. These challenges include, 1) in the 2013 curriculum, there are too many aspects that teachers want to measure and observe for each student, 2) in the independent learning curriculum Teachers must be able to develop religious character education through P5 activities, 3) the characteristics of children raised or the character traits of each child raised, and 4) selecting methods that are in accordance with existing curriculum policies.